Chirality Induction from a Chiral Guest to the Hydrogen‐Bonding Network of Its Hexameric Resorcinarene Host Capsule. Issue 15 (23rd June 2017) - Pollok, Corina H.; Zhang, Qi; Tiefenbacher, Konrad; Merten, Christian
Abstract: The hexameric capsule of resorcin[4]arene1 is capable of encapsulating tertiary amines, which has recently been used in the application of [(1 )6 (H2 O)8 ] as (co‐)catalyst in various asymmetric reactions. However, not much is known about the highly asymmetric but conformationally very dynamic structure of the capsule after uptake of chiral molecules. Therefore, in this contribution, we utilize electronic circular dichroism and vibrational circular dichroism spectroscopy to investigate how several chiral guest molecules affect the structural preferences of the capsule [(1 )6 (H2 O)8 ]. In particular, we show that one small chiral amine encapsulated in [(1 )6 (H2 O)8 ] is sufficient to control and dictate the stereochemical preferences of the entire capsule. Furthermore, neither strong π–π interactions nor a significant steric bulk are required for this induction. The observation of such a chiral imprint of the guest's stereochemistry onto its host molecule is expected to have implications also for other supramolecular capsules. Abstract : Inside out : Using a combined approach of chiroptical spectroscopy and DFT calculations, the authors show that a small chiral amine can induce a chiral conformation to a hexameric resorcin[4]arene capsule.